2010
DOI: 10.1007/s10554-010-9679-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plaque haemorrhage and its age on structural stresses in atherosclerotic plaques of patients with carotid artery disease: an MR imaging-based finite element simulation study

Abstract: Plaque haemorrhage (PH) in atherosclerotic plaques is associated with recurrent thromboembolic ischaemic events. The healing process predominantly involves the repair of the plaque rupture site and the replacement of fresh PH with chronic PH, which is either reabsorbed or replaced by fibrous tissue. The extent to which the presence of PH, and its type i.e. fresh or chronic, affects plaque stability remains unexplored. Finite element analysis (FEA)-based biomechanical stress simulations can provide quantificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Results from ex vivo material testing of AAA specimens showed that material properties of ILTs differ depending on their composition [31, 32]. A previous study on carotid atherosclerotic plaque showed the age of intraplaque haemorrhage can influence the structural stress within a plaque by 30 % [33]. These findings strongly suggest that the use of spatially resolved ILT material properties in computational mechanics simulations may improve the accuracy of AAA wall stress estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Results from ex vivo material testing of AAA specimens showed that material properties of ILTs differ depending on their composition [31, 32]. A previous study on carotid atherosclerotic plaque showed the age of intraplaque haemorrhage can influence the structural stress within a plaque by 30 % [33]. These findings strongly suggest that the use of spatially resolved ILT material properties in computational mechanics simulations may improve the accuracy of AAA wall stress estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The material constants describing different atherosclerotic components are from earlier studies (Sadat et al, 2010b). The pulsatile blood pressure of each patient was used as the loading condition for dynamic simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Aglyamov et al applied model-based elasticity reconstruction method to obtain the Young's modulus of the blood clot during formation and aging of thrombus [39]. Based on their data, least squares fitting method were empioyed to obtain the material parameters for hemorrhage: chronic hemorrhage, Ci=9kPa, Di =9kPa, D2 = 0.25; fresh hemorrhage, c, = 1 kPa, Dj = 1 kPa, D2 = 0.25 [29]. The stress-stretch plots for the material of different components derived from the modified Mooney-Rivlin model were presented in Fig.…”
Section: Fsi Computational Modelmentioning
confidence: 99%
“…However, the discussion about the impact of the IPH on critical mechanical conditions such as plaque wall stress and flow shear stress remains very limited. Sadat et al reported that the aging of hemorrhage would help in plaque stabilization using 2D MRI-based computational modeling [29]. Huang et al determined the potential relationship between PWS and FSS with the location of IPH using FSI models for five human carotid plaques [30].…”
Section: Introductionmentioning
confidence: 99%